Island Mass Effect: A Review of Oceanic Physical Processes - De Falco, Chiara; Desbiolles, Fabien; Bracco, Annalisa; Pasquero, Claudia (Frontiers in Marine Science, 2022)
Increased Net Primary Productivity (NPP) around small islands have been documented worldwide.